Over-indebtedness as a marker of socioeconomic status and its association with obesity: a cross-sectional study - Münster Eva; Rüger Heiko; Ochsmann Elke; Letzel Stephan; Toschke André M (BMC, 2009)
Abstract Background The recent credit crunch will have implications for private households. Low socioeconomic status is associated to various diseases. While income, education and occupational status is frequently used in definitions of socioeconomic status, over-indebtedness of private households is usually not considered. Over-indebtedness is currently increasing in high-income countries. However, its association with health - particularly with obesity - remains unknown. Therefore, the aim of this study was to assess an association between over-indebtedness and overweight or obesity. Methods A cross-sectional study on over-indebtedness and health including 949 over-indebted subjects from 2006 and 2007 in Rhineland-Palatinate and Mecklenburg-Western Pomerania (Germany) and the telephonic health survey 2003 of the Robert Koch-Institute including 8318 subjects, who are representative for the German population, were analysed with adjusted logistic regression considering overweight (BMI ≥25.0 kg/m2) and obesity (BMI ≥30 kg/m2) as response variable. Results After adjusting for socio-economic (age, sex, education, income) and health factors (depression, smoking habits) an independent effect of the over-indebt situation on the probability of overweight (aOR 1.97 95%-CI 1.65-2.35) and obesity (aOR 2.56 95%-CI 2.07-3.16) could be identified. Conclusion Over-indebtedness was associated with an increased prevalence of overweight and obesity that was not explained by traditional definitions of socioeconomic status. Over-indebtedness should be additionally considered when assessing health effects of socioeconomic status.